2012
DOI: 10.3892/or.2012.1694
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effect of evodiamine in SGC-7901 human gastric adenocarcinoma cells via simultaneous induction of apoptosis and autophagy

Abstract: Abstract. Evodiamine, an alkaloid isolated from Evodia rutaecarpa, possesses potent anticancer activity. Although many reports have elucidated the cytotoxic effects of evodiamine in a variety of cancer cells, little is known about the mechanism of evodiamine-induced cytotoxic activity in gastric cancer cells. To date, no report has addressed the synchronized role of autophagy and apoptosis in evodiamineinduced cytotoxic activity. This study was conducted to investigate the synchronized role of autophagy and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 42 publications
1
35
0
Order By: Relevance
“…Therefore, the observation that PDGF-BB increased and evodiamine decreased the expression of p21 in the present study was not unusual. Of note, the inhibitory effects of evodiamine on cell cycle progression have been previously observed in various human tumor cell lines, including small-cell lung cancer cells (20), gastric cancer cells (11), breast cancer cells (21), gastric adenocarcinoma cells (22) and cervical carcinoma HeLa cells (23), and are considered to be important in the antitumor action of evodiamine. The data obtained in the present study extends the current recognition of evodiamine, and suggested that the regulation of cell cycle progression by evodiamine may be general and function in a broader range of cell types, including tumor cells and vascular cells.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, the observation that PDGF-BB increased and evodiamine decreased the expression of p21 in the present study was not unusual. Of note, the inhibitory effects of evodiamine on cell cycle progression have been previously observed in various human tumor cell lines, including small-cell lung cancer cells (20), gastric cancer cells (11), breast cancer cells (21), gastric adenocarcinoma cells (22) and cervical carcinoma HeLa cells (23), and are considered to be important in the antitumor action of evodiamine. The data obtained in the present study extends the current recognition of evodiamine, and suggested that the regulation of cell cycle progression by evodiamine may be general and function in a broader range of cell types, including tumor cells and vascular cells.…”
Section: Discussionmentioning
confidence: 97%
“… 20 , 21 In previous reports, evodiamine induced autophagy and apoptosis in U87-MG glioblastoma and SGC-7901 gastric cancer cells. 22 , 23 In U87-MG cells, autophagy and apoptosis were accompanied by increased cytoplasmic accumulation of calcium. 22 Rasul et al have demonstrated that beclin-1 is involved in evodiamine-induced autophagy in SGC-7901 cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not until these phytochemicals are tested in vitro and in vivo that we can know for sure how far they can go in keeping this disease under control [31-34]. In Thailand gastric cancer is a scourge, however the unusually lower gastric cancer incidences in the Northeastern part of Thailand is of considerable interest.…”
Section: Discussionmentioning
confidence: 99%